PREFERENSI PREFERENSI WISATAWAN DOMESTIK DALAM MEMILIH PRODUK WISATA GASTRONOMI DI KUTA BALI : Indonesia - Komang Renaldi Artha Wijaya; Hanugerah Kristiono Liesteandre; I Gede Gian Saputra (JURNAL GASTRONOMI INDONESIA, 2021)
The purpose of this study is to analyze the preferences of domestic tourists in choosing gastronomic tourism products in Kuta. This study uses online survey activities by determining the sample, namely purposive sampling and large population sample formula. The sample in this study amounted to 200 respondents who had done culinary tourism activities in Kuta. Data were analyzed using conjoint analysis technique. The results of the study indicate that respondents who are domestic tourists, when doing culinary activities in Kuta tend to like neat restaurants, good food, get cooking learning activities, and the price is Rp. 10,000 - Rp. 30,000. In addition, it can also be seen that the store atmosphere attribute is the attribute most considered by domestic tourists in choosing gastronomic tourism products, then followed by quality, price, activity, and the last is service which is less considered.